2018
DOI: 10.1021/acsnano.8b00267
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity and Disorder in the Black Phases of Cesium Lead Iodide Used for Stable Inorganic Perovskite Solar Cells

Abstract: Hybrid organic-inorganic perovskites emerged as a new generation of absorber materials for high-efficiency low-cost solar cells in 2009. Very recently, fully inorganic perovskite quantum dots also led to promising efficiencies, making them a potentially stable and efficient alternative to their hybrid cousins. Currently, the record efficiency is obtained with CsPbI, whose crystallographical characterization is still limited. Here, we show through high-resolution in situ synchrotron XRD measurements that CsPbI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
735
5
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 603 publications
(856 citation statements)
references
References 71 publications
(170 reference statements)
82
735
5
5
Order By: Relevance
“…1.68 eV), which could be assigned to b-CsPbI 3 perovskite.T he XRD patterns of Cs-1.0DMAI and Cs-1.5DMAI samples also exhibited the diffraction peaks at 14.28 8 and 28.68 8,w hich is at ypical diffraction of b-CsPbI 3 perovskite. [10,29] These results suggested that the DMAI content can significantly affect the crystal phase of the final CsPbI 3 perovskite.T he scanning electron microscopy (SEM) was used to explore the morphologies of these different CsPbI 3 thin films.The DMAI content induced different crystallization processes,which lead to the different grain sizes and morphologies of Cs-xDMAI thin films.T he Cs-0.5DMAI thin film exhibits compact thin film with small grain (ca. 100 nm);t he crystal grain size of the Cs-0.7DMAI thin film markedly increases to circa 200-400 nm.…”
Section: Resultsmentioning
confidence: 89%
“…1.68 eV), which could be assigned to b-CsPbI 3 perovskite.T he XRD patterns of Cs-1.0DMAI and Cs-1.5DMAI samples also exhibited the diffraction peaks at 14.28 8 and 28.68 8,w hich is at ypical diffraction of b-CsPbI 3 perovskite. [10,29] These results suggested that the DMAI content can significantly affect the crystal phase of the final CsPbI 3 perovskite.T he scanning electron microscopy (SEM) was used to explore the morphologies of these different CsPbI 3 thin films.The DMAI content induced different crystallization processes,which lead to the different grain sizes and morphologies of Cs-xDMAI thin films.T he Cs-0.5DMAI thin film exhibits compact thin film with small grain (ca. 100 nm);t he crystal grain size of the Cs-0.7DMAI thin film markedly increases to circa 200-400 nm.…”
Section: Resultsmentioning
confidence: 89%
“…CsPbX 3 has four types of crystal polymorph (shown in Figure 1a): [23] the cubic structure (a-, Pm3m); the tetragonal structure (b-, P4/mbm),t he orthorhombic structure (g-, Pbnm); and an on-perovskite structure (d-, Pnma). Thus, for example the RT stable phase of CsPbI 3 is the nonperovskite d-y ellow phase that is relatively inactive as aphotovoltaic material, while what is known as the black (a-) phase is only stable at RT under special conditions.T here are also two other black phases (b and g)t hat are considerably less common.…”
Section: Crystalline Structurementioning
confidence: 99%
“…Nevertheless, the all‐inorganic CsPbI 3 perovskite without any volatile organic component faces serious challenges in terms of low‐phase stability. As this problem was solved, the reversibility of the phase transition was found to be a unique advantage of high‐temperature‐processed inorganic perovskite films . By simply reheating the film at a temperature above the phase‐transition temperature, the undesired yellow‐phase CsPbI 3 will immediately turn back to black‐phase CsPbI 3 , which offers a new route to enhance the long‐term stability of all‐inorganic PSCs .…”
Section: Introductionmentioning
confidence: 99%